Epidemiology, Classification, Clinical Variations and Laboratory Diagnosis of Dermatophytes: A Narrative Review - Khan, Samia Afreen (Bangladesh Journal of Medical Microbiology, 2023)
Dermatophyte is a keratinophilic fungus which can invade keratinized tissue cause dermatophytosis. It is one of the major superficial fungal infections. According to World Health Organization (WHO), 20-25% world population is affected by dermatophytes. Tinea or ring worm infection may have similar feature with other skin diseases. For this reason, identification is necessary in those cases. The aim of this study was to identify different species of dermatophytes causing dermatophytosis at a tertiary care hospital in Bangladesh by Microscopy, culture and PCR Bangladesh Journal of Medical Microbiology, July 2022;16(2):65-71